POWER EFFICIENT MINI INVERTER (International Journal of Food and Nutritional Sciences, 2021)
Inverters are extensively used in both residential and commercial settings to serve as a backup power source in the event of a power outage from the utility grids. In the case of a power outage, an inverter powers the electric equipment. As the name suggests, an inverter converts AC to DC to charge the battery before inverting DC to AC to power the electronic devices. So here is a power efficient converter that is compact in size and can provide an output voltage of 220v-230/150w. This energy-efficient mini inverter can be used to power items such as WiFi networks, mobile charges, lights, and so on